Psychometric properties of the strategy inventory for language learning in Peruvian university students - Saez-Zevallos, Nataly Susan; Cunza-Aranzábal, Denis Frank; Abanto-Ramírez, Carlos D.; Montalvo-Apolín, Danitza Elfi (Frontiers in Education, 2025)
BackgroundIn contemporary academia, proficiency in a second language, particularly English, is of significant importance for university students. The objective of this research is to determine the validity and reliability properties of the Strategy Inventory for Language Learning (SILL) among Peruvian university students.MethodsSix hundred ten Peruvian university students, aged between 18 and 50 years (M = 22.8; SD = 5.90), participated in the study. Statistical techniques for latent variables were employed, and recommendations for determining the psychometric properties of educational and psychological tests were followed.ResultsThe results show that the SILL exhibits an internal structure organized into six first-order factors and one second-order factor, consistent with the theoretical proposal. This structure was confirmed through CFA with excellent goodness-of-fit indices (χ2 = 222.254, df = 129, p = 0.000, RMSEA = 0.034, SRMR = 0.037, CFI = 0.971, TLI = 0.966). The inventory also demonstrates adequate internal consistency for its six factors, as well as for the complete inventory (α/ω/H > 0.7), and is invariant according with gender (male and female), geographical location (coast, mountains and jungle) age (late adolescence and early adulthood), and English educational level (A and B).ConcussionIt’s concluded that the SILL is a measurement instrument that demonstrates validity, factorial invariance, and high reliability in its scores. Consequently, it can be utilized in future academic research.